KINERJA KEUANGAN BANK MAYAPADA 2007-2025: ANALISIS DESKRIPTIF ATAS RASIO KEUANGAN PERBANKAN - Agus Sulistyono; Muhammad Yusuf; Osly Usman; Muhammad Rafli; Rika Vebina Tarigan (POLITEKNIK LP3I JAKARTA, 2026)
This study analyzes the financial performance of PT Bank Mayapada Internasional Tbk during 2007-2025 using a descriptive quantitative approach based on secondary data from annual reports. The indicators include total assets, loans, third-party funds, equity, net income, CAR, Gross NPL, ROA, ROE, NIM, BOPO, and LDR. The analysis applies financial ratios, trend analysis, annual growth, CAGR, and periodization. The findings show that Bank Mayapada recorded strong balance sheet expansion. Total assets increased from Rp4.47 trillion in 2007 to Rp163.83 trillion in 2025, with a CAGR of 22.14%. However, this growth was not followed by sustainable profitability. ROA declined from 1.46% to 0.03%, while BOPO rose to 99.59%. These results indicate pressure on earnings quality, operational efficiency, asset quality, and net interest margin recovery. The study implies that bank asset growth cannot be viewed as a sufficient performance measure without sound credit quality, cost efficiency, capital adequacy, and profitability. Managerially, the bank should strengthen risk-based lending, productive asset optimization, BOPO control, funding cost management, and credit analytics digitalization. For investors, this study highlights integrated assessment of profitability, credit risk, liquidity, efficiency, and capital. For future research, the findings support causal tests and comparative studies among banks with similar national capital groups.